Implementasi Manajemen Waktu pada Siswa Sekolah Dasar - Putra, Alan Anditia; Daflaini, Daflaini; Pohan, Munawir (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2022)
This research aims to find out thematic real work lectures (KKN) based on religious moderation for students of the State Islamic Religious Institute (IAIN) in detail "implementation of time management for elementary school students". The objects of this research are Islamic boarding schools and Al-Quran educational parks in the village of Tebing Tinggi, Tapan, Alam Ampek Hulu Tapan sub-district, South Coast district. Based on what we have done, the results show that students are able to make a daily schedule for activities properly and correctly so that students can apply it in their daily life. This research method is descriptive qualitative, which is a field study that reveals, finds and explores various information about the implementation of time management in elementary school students. Writers must also understand and interpret the data and present it in the form of stories and narratives. The data sources used in this research are observation, interviews and documentation.